2017
DOI: 10.1186/s13643-017-0443-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between adverse pregnancy outcomes and maternal human papillomavirus infection: a systematic review protocol

Abstract: BackgroundHuman papillomavirus (HPV) is the most prevalent genital infection, especially in young women of reproductive age. In vitro and animal model experiments provide compelling evidence of the harmful effect of HPV on pregnancy outcomes, but results from epidemiologic studies are inconclusive. We aim to determine the strength of the relationship between adverse pregnancy outcomes (APO) and HPV infection and assess its consistency across studies, by systematically reviewing the literature.MethodsThe search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…Ambuhl showed that HPV infection, alone, is significantly associated with, and may cause, spontaneous abortions and preterm deliveries (Ambuhl, ); these findings are supported by Niyibizi, Zanré, Mayrand, & Trottier () and Cho []. Mosbah, Barakat, Nabiel, & Barakat () found an association between active HPV infection and spontaneous preterm labor, and showed a direct correlation between viral load and preterm labor.…”
mentioning
confidence: 79%
“…Ambuhl showed that HPV infection, alone, is significantly associated with, and may cause, spontaneous abortions and preterm deliveries (Ambuhl, ); these findings are supported by Niyibizi, Zanré, Mayrand, & Trottier () and Cho []. Mosbah, Barakat, Nabiel, & Barakat () found an association between active HPV infection and spontaneous preterm labor, and showed a direct correlation between viral load and preterm labor.…”
mentioning
confidence: 79%
“…It has also been reported in various studies that within 1-2 years of HPV infection almost 80% of them resolve spontaneously [15]. Various studies suggested that during pregnancy it is more likely to acquire and progress HPV infection [16] which regresses after delivery [6,7,17,18].…”
Section: Incidence Of Hpv Infection In Pregnant Women Populationmentioning
confidence: 90%
“…The changed immune response and hormonal milieu during pregnancy might favor the presence or persistence of the HPV infection. Niyibizi et al [18] reported the prevalence of HPV infection in pregnant women with a wide variation from 5.5 to 65%. Various HPVs in several populations have been reported to be associated with adverse pregnancy outcomes such as preeclamsia, preterm rupture of membranes (PROM), preterm delivery, fetal growth restriction and placental abnormalities.…”
Section: Incidence Of Hpv Infection In Pregnant Women Populationmentioning
confidence: 99%
“…As it is already known, HPV is the most common sexually transmitted infection in adults [12]. In previous researches, maternal infections, inflammation [13], and changes in vaginal bacterial microbiota [14] have been recognised as an underlying cause of major adverse pregnancy outcomes: miscarriage [15], spontaneous preterm birth [16], and hypertensive disorders related to pregnancy [17,18].…”
Section: Discussionmentioning
confidence: 99%